A study on vegetative propagation of Huperzia serrata by cuttings in Sa Pa, Lao Cai - Anh, Le Thi Lan; Anh, Bui Tuan; Sang, Giang Xuan; Dat, Ton That Huu; Huong, Ho Thi; Thanh, Nguyen Duc; Thuy, Le Thi Bich (Academia Journal of Biology, 2019)
Huperzia serrata is a precious medicinal plant used in medicine to support and treat Alzheimer’s disease. Currently, this species is in danger of extinction due to indiscriminate exploitation for commercial purposes. Furthermore, this species reproduces slowly and is difficult to cultivate artificially. The reproduction by spores of this species is very long and takes 15−20 years from the spore germination to mature plant, whereas asexual reproduction by tissue culture is also difficult. Therefore, cutting is an effective method to propagate this species on a large scale. In this study, we surveyed the factors affecting the survival rate, the rooting and the number of new leaves of the stem cuttings, including cutting length, growing substrate, and effects of growth-regulating hormones IBA (0 ppm, 500 ppm, 1000 ppm, 2000 ppm and 3000 ppm) and α-NAA (0 ppm, 10 ppm, 20 ppm, 30 ppm and 40 ppm). The experimental results showed that using cuttings of 6 cm in length treated with IBA at a concentration of 1000 ppm for 30 mins and cultured on the substrate mixture of soil, decomposed animal manure and rice husk at a ratio of 3:1:1 was the best for cuttings of H. serrata in Sa Pa. The results of this study will contribute to the conservation and development of genetic source of H. serrata in Vietnam.